System dynamics modeling for developing an agrotourism-creative economy in the framework of the village innovation system - Santoso, Sugeng; Widyanty, Winda; Nurhidajat, R.; Ramadhani Marfatah, Muhammad; Mahmud, Gustofan; Fahlevi, Mochammad; Aljuaid, Mohammed; Zhghenti, Tsotne; Shahid, Duaa (Frontiers in Environmental Science, 2022)
Cibodas village is one of the villages in the regency of West Bandung, which shows potential for agrotourism and a creative economy. However, the dynamic environmental changes in the post-COVID-19 era have presented challenges to developing these economic potentials. Therefore, creating a model to develop agrotourism and a creative economy in Cibodas village is necessary. This study aims to create a system dynamics model with a causal loop diagram (CLD) based on the village innovation system framework to develop the agrotourism-creative economy in Cibodas village. Both qualitative and quantitative approaches are used to identify the main variables and to develop and review the CLD. The quantitative approach provides researchers with three main variables that must be involved in the study, namely, the general innovation infrastructure, specific industrial clusters, and intermediation. The three variables are interrelated and form a CLD. The formed CLD was further explored with a qualitative approach in the form of an in-depth interview and focus group discussions (FGDs) with several key informants: the Head of the Agronative Cooperative, the Head of Cibodas Village, and the Regency Tourism and Culture Office (Disparbud) of West Bandung. Based on the results of the scenario for the existing conditions for a 24-month period, it was found that the innovation infrastructure variables had increased by 10.94% and the intermediation variables had increased by 0.22%. The simulations were carried out by increasing the intermediation intervention twice as much as that of the existing conditions. Hence, the innovation infrastructure variables increased by 18.01% and the intermediation variables increased by 0.05%. Cibodas village would take advantage of these R & D products to help its creative economy actors produce more products having a high-selling value. Moreover, by employing this strategy, they could also help their creative economy actors increase the absorption of an innovation to have such a high competitiveness.